2015
DOI: 10.1080/19443994.2013.846236
|View full text |Cite
|
Sign up to set email alerts
|

Batch adsorption of methylene blue from aqueous solutions by untreated Alfa grass

Abstract: In this study, adsorption capacities of untreated Alfa stems were tested for the removal of methylene blue (MB) as a dye in aqueous solutions. The effects of initial dye concentration (10-150 mg/L), contact time, adsorbent dose (0.25-12.5 g/L), solution pH (2-12), temperature (283-330 K) and ionic strength (5-100 mg/L) on MB adsorption were investigated. The thermodynamic parameters, the kinetics and the factors controlling the adsorption process were also calculated and discussed. The experimental data modell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…The pH pzc of ALP was calculated using the solid addition method [23][24][25] and was determined to be 6.3 (Table 3). Similar results (pH pzc 6.8) were observed for Alfa stems [26] and for meranti sawdust (pH pzc 6.23) [25]; however, for the extracted Alfa fibers, a pH pzc value of 7.7 was obtained [27].…”
Section: Characterization Of Alpsupporting
confidence: 70%
“…The pH pzc of ALP was calculated using the solid addition method [23][24][25] and was determined to be 6.3 (Table 3). Similar results (pH pzc 6.8) were observed for Alfa stems [26] and for meranti sawdust (pH pzc 6.23) [25]; however, for the extracted Alfa fibers, a pH pzc value of 7.7 was obtained [27].…”
Section: Characterization Of Alpsupporting
confidence: 70%
“…It was reported that cationic dye adsorption is favored at pH greater than pH pzc because of the presence of functional groups such as the OH À group, whereas anionic dye adsorption is favored at pH less than pH pzc , where the surface becomes positively charged. 32,33 Investigating the optimum pH of the solution is a continuing concern by researchers within the adsorption process. Hameed et al 34 studied methylene blue (MB) eradication from an aqueous solution based on papaya seeds adsorbent.…”
Section: Effect Of Phmentioning
confidence: 99%
“…Results of experiments in the literature review have shown high adsorption capacities of the various affordable adsorbents for MB removal 10 . While some adsorbents such as peanut shell 11 , coconut fiber 12 , Alfa grass 13 , sugarcane bagasse 14 , and pine sawdust 15 are used without any modification, some others are utilized subsequent to diverse treatments including phosphoric acid treatment 16 , magnetization 17 , ZnCl 2 activation 18 , etc. or pretreatment sorbents by low-cost materials including Rosa damascene 8 cellulose and its salts 19 and oak wood 20 .…”
Section: R a F Tmentioning
confidence: 99%